New Viruses Infecting Hyperthermophilic Bacterium Thermus thermophilus - Matvey Kolesnik; Constantine Pavlov; Alina Demkina; Aleksei Samolygo; Karyna Karneyeva; Anna Trofimova; Olga S. Sokolova; Andrei V. Moiseenko; Maria Kirsanova; Konstantin Severinov (Viruses)
Highly diverse phages infecting thermophilic bacteria of the Thermus genus have been isolated over the years from hot springs around the world. Many of these phages are unique, rely on highly unusual developmental strategies, and encode novel enzymes. The variety of Thermus phages is clearly undersampled, as evidenced, for example, by a paucity of phage-matching spacers in Thermus CRISPR arrays. Using water samples collected from hot springs in the Kunashir Island from the Kuril archipelago and from the Tsaishi and Nokalakevi districts in the Republic of Georgia, we isolated several distinct phages infecting laboratory strains of Thermus thermophilus. Genomic sequence analysis of 11 phages revealed both close relatives of previously described Thermus phages isolated from geographically distant sites, as well as phages with very limited similarity to earlier isolates. Comparative analysis allowed us to predict several accessory phage genes whose products may be involved in host defense/interviral warfare, including a putative Type V CRISPR-cas system.